1967
DOI: 10.1099/00221287-49-2-277
|View full text |Cite
|
Sign up to set email alerts
|

Inducible  -lactamase in Enterobacter

Abstract: S U M M A R YProduction of P-lactamase by nine strains of the genus Enterobacter (eight Enterobacter cloacae, one E. aerogenes) was studied to determine its inducibility. Induction was observed with benzylpenicillin (500 ,ag./ml.) in all except one strain. Cultures were examined to locate the enzyme; it was found that in exponential growth the enzyme was cell-bound, and in stationary phase cultures much of it was in the culture medium. Maximum enzyme activity was only demonstrated after cell-breakage. Substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 7 publications
3
39
0
1
Order By: Relevance
“…As to $-lactamases used in this experiment, penicillinase is a constitutive enzyme while cephalosporinase is generally inducible. It was also reported that cephalosporinases produced by strans of Pseudomonas [12,18] and Enterobacter [10] are inducible enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…As to $-lactamases used in this experiment, penicillinase is a constitutive enzyme while cephalosporinase is generally inducible. It was also reported that cephalosporinases produced by strans of Pseudomonas [12,18] and Enterobacter [10] are inducible enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Se inició con un cultivo de 24 horas del aislamiento clínico de E. cloacae, el cual se ajustó a una población de microorganismo equivalente a 0,5 en la escala de McFarland, y se incubó a 37 °C durante dos horas. A continuación se adicionó penicilina G como inductor de la producción de enzima en tres concentraciones diferentes, 0,5; 1,0; 2,0 mg/ml, y se incubó durante cinco horas con agitación continua con el fin de estandarizar la concentración efectiva para la inducción (44,45). Para lograr este propósito se determinó el porcentaje de hidrólisis del nitrocefín de cada uno de los extractos crudos de betalactamasa durante diferentes tiempos de incubación, los ensayos espectrofotométricos se realizaron haciendo el seguimiento a la hidrólisis del nitrocefín (100 μM) a una longitud de onda de 486 nm durante 60 minutos y a una temperatura de 20 °C (46).…”
Section: Evaluación De La Actividad Inhibitoria Del Compuestounclassified
“…The genes ampR and ampC have been found in many organisms (93)(94)(95)(96)(97). In systems with inducible ampC, the ampR gene is always present adjacent to ampC but is divergently transcribed (98)(99)(100).…”
Section: Transcriptional Regulation Of the ß-Lactamase Ampcmentioning
confidence: 99%
“…The amp genes were first discovered in Enterobacter cloacae to confer resistance to β-lactams (93) and later in other members of Enterobacteriaceae (94)(95)(96)(97). The products of amp genes in E. cloacae and other organisms include the AmpC β-lactamase, the AmpG permease, a putative AmpE permease, the AmpD cytoplasmic amidase, and the transcriptional regulator AmpR (93)(94)(95)(96)(97).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation